2021
DOI: 10.3390/ijms221910592
|View full text |Cite
|
Sign up to set email alerts
|

RNA Modifications and Epigenetics in Modulation of Lung Cancer and Pulmonary Diseases

Abstract: Lung cancer is the leading cause of cancer-related mortality worldwide, and its tumorigenesis involves the accumulation of genetic and epigenetic events in the respiratory epithelium. Epigenetic modifications, such as DNA methylation, RNA modification, and histone modifications, have been widely reported to play an important role in lung cancer development and in other pulmonary diseases. Whereas the functionality of DNA and chromatin modifications referred to as epigenetics is widely characterized, various mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 144 publications
0
57
0
Order By: Relevance
“…In this study, stemness-related biomarkers were positively associated with the risk score, demonstrating the prognostic value of the formula. Modification of m 6 A, m 5 C, m 1 A, and m 7 G are the common type of modification in RNA and plays critical roles in cancer development ( Teng et al, 2021 ; Xu F. et al, 2021 ; Xu R. et al, 2021 ). And RNA methylation highly interconnected with hypoxia, immune response and EMT( Lin et al, 2019 ; Chao et al, 2020 ; Wang E. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, stemness-related biomarkers were positively associated with the risk score, demonstrating the prognostic value of the formula. Modification of m 6 A, m 5 C, m 1 A, and m 7 G are the common type of modification in RNA and plays critical roles in cancer development ( Teng et al, 2021 ; Xu F. et al, 2021 ; Xu R. et al, 2021 ). And RNA methylation highly interconnected with hypoxia, immune response and EMT( Lin et al, 2019 ; Chao et al, 2020 ; Wang E. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, m7G methylation modifications have attracted increasing attention. Methyltransferase-like 1 (METTL1) is a writer of m7G methylation ( 30 ). Recent studies also reported that METTL1 is involved in tumor development by promoting mRNA processing in an m7G-dependent manner ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…M6A modification, the most common epigenetic methylation modification in mammalian mRNA and lncRNA, participates in almost every process of RNA metabolism (Dai et al 2018). Convincing evidence indicated that m6Amodification of lncRNAs plays a critical regulatory role in the development and progression of lung cancer (Teng et al 2021). For example, ALKBH5-mediated m6A demethylation of lncRNA RMRP promotes tumorigenesis of LUAD in vitro and in vivo (Yu and Zhang 2021).…”
Section: Discussionmentioning
confidence: 99%